Personality traits affect teaching performance of attending physicians: results of a multi-center observational study. - Renée A Scheepers; Kiki M J M H Lombarts; Marcel A G van Aken; Maas Jan Heineman; Onyebuchi A Arah (PLoS ONE)
Background Worldwide, attending physicians train residents to become competent providers of patient care. To assess adequate training, attending physicians are increasingly evaluated on their teaching performance. Research suggests that personality traits affect teaching performance, consistent with studied effects of personality traits on job performance and academic performance in medicine. However, up till date, research in clinical teaching practice did not use quantitative methods and did not account for specialty differences. We empirically studied the relationship of attending physicians' personality traits with their teaching performance across surgical and non-surgical specialties. Method We conducted a survey across surgical and non-surgical specialties in eighteen medical centers in the Netherlands. Residents evaluated attending physicians' overall teaching performance, as well as the specific domains learning climate, professional attitude, communication, evaluation, and feedback, using the validated 21-item System for Evaluation of Teaching Qualities (SETQ). Attending physicians self-evaluated their personality traits on a 5-point scale using the validated 10-item Big Five Inventory (BFI), yielding the Five Factor model: extraversion, conscientiousness, neuroticism, agreeableness and openness. Results Overall, 622 (77%) attending physicians and 549 (68%) residents participated. Extraversion positively related to overall teaching performance (regression coefficient, B: 0.05, 95% CI: 0.01 to 0.10, P = 0.02). Openness was negatively associated with scores on feedback for surgical specialties only (B: -0.10, 95% CI: -0.15 to -0.05, P<0.001) and conscientiousness was positively related to evaluation of residents for non-surgical specialties only (B: 0.13, 95% CI: 0.03 to 0.22, p = 0.01). Conclusions Extraverted attending physicians were consistently evaluated as better supervisors. Surgical attending physicians who display high levels of openness were evaluated as less adequate feedback-givers. Non-surgical attending physicians who were conscientious seem to be good at evaluating residents. These insights could contribute to future work on development paths of attending physicians in medical education.